Strategi Mitigasi Risiko Pembiayaan Muḍarabah pada Baitul Maal wat Tamwil (BMT) - Lin Sururoh; Miftahur Rahman; Achmad Abdul Fatah (Kartika: Jurnal Studi Keislaman, 2026)
Risk management is an important aspect in maintaining the sustainability of Islamic financial institutions, particularly in muḍarabah financing, which is characterized by profit-sharing but also involves risks of loss and uncertainty. This study aims to analyze the risk mitigation strategies implemented by USPPS BMT An-Nawawi Berjan Purworejo in managing muḍarabah financing. The research method employs a qualitative approach with descriptive analysis, utilizing documentation, interviews with managers, marketing staff, and employees, as well as references from reliable sources. Data analysis techniques include reduction, display, and verification, while data validity is examined through triangulation. The findings indicate that risk mitigation strategies are effective, as evidenced by the annual decline in non-performing financing (NPF). The main strategy applied is reconditioning in risk management. Internal obstacles include employees’ lack of focus in analyzing prospective customers, while external obstacles arise from muḍarib customers who demonstrate poor intentions in fulfilling their obligations. Overall, the implementation of risk mitigation strategies at USPPS BMT An-Nawawi Berjan can be considered successful, as it minimizes problematic financing and supports the sustainability of muḍarabah products